CHARACTER DETECTION IN BNI INTERNET BANKING CAPTCHA IMAGE USING TEMPLATE MATCHING CORRELATION - Sutaji, Deni (LPPM of STIMIK ESQ, 2019)
Captcha image is already used in Internet Banking as a security device in the process of authentication for active users as a humans or a robots. BNI Bank is the one that applies capthca image, contain four number characters in it. In this study, we propose how to read characters in the captcha image using Template Matching Correlation method. Later in the next study it can be used as an automatic login system for Micro, Small and Medium Enterprises (MSME) players who apply transfer payments to BNI Bank accounts. The first step to recognize is pre-processing, then proceed with segmentation and labeling per characters, and the last is matching with a reference template dataset using Template Matching Correlation. Of the 100 test data, this system produces an accuracy rate that reaches 100%. So this method is suitable for identifying characters of captcha image on the BNI Internet Banking login page.